Can higher education contribute to trust building in a fragmented reality? A Latin American perspective - Danilo Romeu Streck; Maria Julieta Abba; Paulina Latorre; Carolina Schenatto da Rosa (Emerald Publishing, 2024)
Purpose - The article aims at exploring the challenges and possibilities of cooperation of higher education in a Latin American social, political and cultural context that faces historical difficulties of integration, as well as the potential contribution of academic cooperation for global citizenship. Design/methodology/approach - The paper presents a general overview of networks and international centers of academic cooperation of higher education in Latin America. The analysis comprises objectives, countries, stakeholders, activities, projects and scope. The study is based on literature on internationalization, regional integration and the development of higher education, as well as on empirical gathered with networks/centers and key actors in the field. This study was carried out as a mixed qualitative method design. Firstly, a systematic review of a literature corpus of studies produced by Latin-American scholars was performed. Semi-structured interviews were then carried out with a group of scholars who are members of networks. Findings - The findings include a review of the role of higher education in a politically fragmented reality, a panorama of major networks and international centers of academic cooperation with emphasis on internationalization of higher education, as well as their connections. The are highlighted examples of successful initiatives of cooperation and, based on interviews, there is presented a preliminary view on cooperation and trust building from professionals in higher education in Latin America. Originality/value - In the last decades, with the growing interest and need for internationalizing higher education, many universities have organized or joined networks and international centers. The article will contribute for mutual knowledge of these spaces, their shortcomings and potentials, thus creating conditions for dialogue among them, as well as with universities in other continents.